Results from the Australian 2022 Report Card on physical activity for children and young people - Kylie D. Hesketh; Verity Booth; Verity Cleland; Sjaan R. Gomersall; Tim Olds; Lindsey Reece; Nicola D. Ridgers; Leon Straker; Michalis Stylianou; Grant R. Tomkinson; David Lubans (Journal of Exercise Science & Fitness, 2023)
Background/Objective: Past Physical Activity Report Cards have indicated a minority of Australian children and young people are sufficiently active. The purpose of this paper is to summarise grades across 10 indicators of the 2022 Australian Physical Activity Report Card, to assess physical activity behaviours and supports. Methods: A development team consisting of research experts synthesised and evaluated national and state level data to inform grades for each indicator. Data were drawn from nationally and state/territory representative datasets spanning 2016–2021. Results: Overall Physical Activity Levels and Screen Time were both assigned grades of D-, remaining the worst performing indicators. Australia's best performing indicator was Community and the Built Environment (A-), followed by Organised Sport and Physical Activity (B-). Remaining indicators were Family and Peers (C+), School (C+), Strategies and Investments (C-), Active Transport (D-) and Physical Fitness (D-). Active Play was unable to be graded, due to lack of consensus on a primary metric for this indicator and a lack of representative data. Conclusion: Evidence suggests that physical activity levels of Australian children remain consistently low, despite access to and availability of facilities and open spaces. There is a strong need for a National Physical Activity Plan to address this. The theme for the 2022 Australian Physical Activity Report Card, REBOOT! Reimagining physically active lives encourages us all to think more imaginatively about how we might engage all children and young people through diverse physical activity opportunities to be more active.